Neural networks for facility location problems (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2019)
This paper presents a new self-organizing neural network approach for solving graph-based facility location problems. It is designed to have small amount of parameters and to not need much tuning. We test our approach on several groups of problems and show that it consistently finds good feasible solutions.